Budget Deficit, Debt, and Inflation in Ghana (1960-2022): The Fiscal Theory of Inflation Case? - SEIDU, Abdul Majeed; VASILEV, Aleksandar (Theoretical and Practical Research in Economic Fields; Vol 15 No 1 (2024): TPREF, Volume XV, Issue 1(29), Spring 2024DO - 10.14505/tpref.v15.1(29).10, 2024)
This study follows the approach in Kehoe and Nicolini (2021) in order to analyse and interpret the historical performance of Ghana’s economy over the period 1960-2022 in terms of deficits, public debt accumulation, monetary policies and their relationships to inflation, exchange rate etc. The paper explores the link and similarities between Ghana’s economic cycle from pre- and post-military rule. In both cases, excessive borrowing, leading to a large accumulation of public debt, and accompanied with burdensome debt interest payments, has been one of the major challenges that the country must wean itself from. The study also documents that the underlying reason for the deficits is the low domestic revenue mobilisation, i.e the fiscal capacity of Ghana is lower compared to the one of developed countries. Finally, the positive interaction between money supply and inflation has also been established in this study. However, the increase in money supply (and thus inflation) is a result of fiscal imbalances: by printing money, the Central Bank of Ghana is effectively using inflation as a tax and trying to generate a seigniorage revenue to “cover” at least part of the budget deficit.